Research on the Transaction Mechanism and Benefit of Promoting New Energy Consumption - Jianhua YANG; Xiongfei WANG; Daqiang XIAO; Jiawei ZHAO; Dunnan LIU (Zhongguo dianli)
Based on the problems for promoting high proportion of new energy consumption, this paper firstly constructs a contribution model of market mechanism to new energy consumption, aiming at the three market mechanisms of power generation rights trading, standby ancillary services trading and time of use (TOU) electricity price trading of self-owned power plants. Secondly, based on the market mechanism of promoting new energy consumption, the paper analyses the environmental benefits, benefits of saving electricity purchasing cost, and benefits of improving power supply reliability for promoting new energy consumption, and constructs a quantitative model to quantify the benefits of market mechanism. Finally, the data of northwest and southeast coastal areas are selected to calculate the benefits. The results show that the effective market mechanism can promote the high proportion of new energy consumption, while bringing considerable benefits.